X-ray photoelectron spectroscopy study on sintered Pb1-xLaxTiO3 ferroelectric ceramics - Mastelaro, Valmor R.; Lisboa-Filho, Paulo N. [UNESP]; Neves, Person P.; Schreiner, Wido H.; Nascente, Pedro A.P.; Eiras, José A. (Elsevier, 2007)
The Pb1-xLaxTiO3 sintered ferroelectric ceramics with x equal to 0, 0.10, 0.15, 0.20, and 0.30 were studied by X-ray photoelectron spectroscopy (XPS). The binding energy of the Ti 2p lines is consistent with only one chemical state, Ti4+. On the other hand, in the case of Pb 4f and O 1s XPS spectra, apart from the main peaks attributed to the lattice ions, minor peaks related to the surface states were also observed. The presence of Pb0 state on the surface of all samples was due to the reduction of lead ions caused by the preferential removal of the oxygen ions after sputtering. The non observation of Ti3+ ions confirms that the mechanism of charge compensation that should occurs owing to the substitution of Pb2+ by La3+ is due to the preferential formation of Pb site vacancies, and not to a reduction from Ti4+ to Ti3+ states. Within the limits of the present experiment, there is no evidence of the existence of non-equivalent Pb, Ti, and La sites as the Pb1-xLaxTiO3 ceramic changes from a normal to a relaxor ferroelectric state. © 2006 Elsevier B.V. All rights reserved.
Keywords: Electronic structure; Ferroelectric ceramics; Pb1-xLaxTiO3; Relaxor